The progestogen challenge test in postmenopausal women: clinical and morphologic aspects - Bortoletto, Claudia de Carvalho Ramos; Baracat, Edmund Chada; Gonçalves, Wagner José; Stávalle, João Norberto; Lima, Geraldo Rodrigues de; Novo, Neel Ferreira (São Paulo Medical Journal, 1996)
The clinical aspects and anatomopathological patterns of 150 postmenopausal women were studied using the progestogen challenge test. An endometrial biopsy was obtained and submitted to the progestogen test. A histopathological analysis of the uterine mucosa from women with a positive progestogen test revealed that the endometrium was active in 44 percent of cases and atrophic or inactive in 56 percent. In contrast, among women with a negative response, the endometrium was atrophic in 94 percent of cases and active in 6 percent. Analysis of clinical aspects did not show significant differences between groups in terms of age; age at menarche and at menopause; fasting blood glucose levels; or body mass. However, postmenopausal time was significantly shorter for women with a positive test, with a correlation between postmenopausal time of one to two years and test positivity. The progestogen challenge test for the detection of atrophic endometrium presented 78.57 percent sensitivity, 77.05 percent specificity, 44 percent positive predictive value, and 94 percent negative predictive value. Thus, when negative, the test is highly valuable, indicating the presence of atrophic endometrium in 94 percent of cases. False-negative results occurred in only 6 percent of the subjects, with no case of hyperplasia detected. However, when the response to the test was positive, the endometrium was atrophic in 56 percent of the cases. We suggest that, in order to avoid invasive procedures, the progestogen challenge test be combined with other methods such as transvaginal ultrasonography.